Proyecto de factibilidad para la creación de una empresa productora de caja típica con diseño exclusivo y productos tradicionales y su comercialización en la ciudad de Loja - Loaiza Andrade, Zaura Zoraima (2015)
Considering the need tohave an artistic, traditionaland exclusiverepresentative of the cityofLojaproduct;it is proposed toimplement thisproject with theoverall objectivea draft anfeasibility projectfor creation ofa producer oftypicalbox withexclusive designand traditionalproducts and their marketingin the city ofLoja. To determine the feasibilityandthe implementationof the project andmeetits objectives, I used several methods; inductive, deductive, analytical, syntheticand historical; and research techniquessuch as directobservation andsurvey; theyallowed me tomeetall the requirements forthedevelopment of this work. The document presents four important studies: market survey; technical study, administrative study, and financial study. According to the results shown in the market study carried on the economical active population of Loja, the potential demand is 101.671 people who know the product; the real demand displays a total of 62.430 real demanders. Results show then that the effective demand sums up 41.776 users who would buy the product to the new company; with an average purchase of 4 cases annually, the unsatisfied demand of the product shows a result of 167.104 cases. On the other hand, there is no offer of the product in the city of Loja because there is no registered company that produces nor sells cases with exclusive design and traditional products. The technical study establishes the size and location of the project, which will be located on the San Sebastián neighborhood, at 14-75 Lourdes St, between Sucre and Bolivar St, in Loja city. The facility has all utilities included, an annex of the plant facility drawings is attached, and the same portrays the productive process of the company. The administrative study proposes the legal organization of the new company as a unipersonal enterprise, which business name is LOJANITOS. The administrative organization scheme is presented trough an organization chart and an operations manual of the company. The financial study exposes that an investment of $16.032, 81 is required in order to create the company. The owner of the company will contribute with the 50, 10% of the total investment and the 49,90% with a loan of US$800.000. The financial report indicates that the liquid net income is $ 22.353,88 within the first financial recovery period. The cash-flow sums a total of $ 23.555,62 during the first year. On the evaluation report it is clear that the net present value is positive with a total of $168.782,86. The internal return rate is 158,89%, which is to say that it is bigger than the capital opportunity cost of 11,20 %. The cost-benefit relation indicates that for each invested dollar an outcome of $ 0,42 will be obtained. The time required to recover the original investment is 8 months 6 days. For this project, the sensitivity values are lower than 1, therefore not affecting the project changes in costs and revenues increased 29,53%; and diminished by 21.21% respectively, that is to saythe project is not sensitive to these changes. And conclusions and recommendations were determined. All of these data demonstrates that this project is feasible and profitable; hence it is recommended its execution, for its importance in Loja’s city development.